# Sum of First $n$ Squares Equals $\frac{n(n+1)(2n+1)}{6}$

I am just starting into calculus and I have a question about the following statement I encountered while learning about definite integrals:

$$\sum_{k=1}^n k^2 = \frac{n(n+1)(2n+1)}{6}$$

I really have no idea why this statement is true. Can someone please explain why this is true and if possible show how to arrive at one given the other?

If you know that the nth square is the sum of the first n odd numbers, you can rewrite each square in the above sum in that way and do a little bit of rearranging to get the desired identity. In general, knowing the value of (n + 1)^k - n^k allows you to write (n+1)^k as a telescoping sum of a polynomial of degree k-1, running over the values 1 through n. If you know the values of the sums of consecutive powers up to k-1, this allows you to find the sum of consecutive kth powers by substituting the polynomial sum for each kth power.

Another method by using telescoping sum :- We know $(a+b)^3-a^3-b^3=3ab(a+b)$ , take

$a=k-1 , b=2$ , then $a+b=k+1$ and $(k+1)^3-(k-1)^3-2^3=6(k-1)(k+1)=6k^2-6$ ,

hence $(k+1)^3-(k-1)^3-8+6=(k+1)^3-k^3+k^3-(k-1)^3-2=6k^2$ , taking sum over $k$

from $1$ to $n$ we get , $\sum_{k=1}^n [(k+1)^3-k^3] + \sum_{k=1}^n [k^3-(k-1)^3] -\sum_{k=1}^n 2 = 6 \sum_{k=1}^nk^2$ , the first

sum on the left hand side is telescoping resulting in $(n+1)^3-1$ , the second sum is also telescoping resulting in $n^3-(1-1)^3=n^3$ , and the third sum is simply $2n$ , hence

$6 \sum_{k=1}^nk^2=(n+1)^3-1+n^3-2n=2n^3+3n^2+n=n(n+1)(2n+1)$